2005
DOI: 10.1542/peds.2004-1482
|View full text |Cite
|
Sign up to set email alerts
|

Early Death, Morbidity, and Need of Treatment Among Extremely Premature Infants

Abstract: The survival rate was high and the morbidity rate at discharge home was low in the present study, compared with previous population-based studies. With the exception of ROP, the morbidity rates among the survivors were not higher at the lowest GAs, possibly because withholding treatment was considered more acceptable for the most immature infants. The need for intensive care increased markedly for survivors with the lowest GAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
222
6
21

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(274 citation statements)
references
References 29 publications
25
222
6
21
Order By: Relevance
“…18 In more recent studies, none of the infants born at <23 weeks were reported to survive to discharge from the NICU. [19][20] It appears that these findings, and perhaps the practicing neonatologists' own experiences, have influenced the approach to the management provided in the delivery room to the smallest and most immature neonates, as a recent survey of academic and private neonatologists in the United States has found that only 4% of the participants would resuscitate a neonate at 23 weeks' gestation with a birth weight of <500 g. 12 It further states that 57% of the responders would provide comfort care only, and 36% would defer the decision to parental wishes for these extremely immature infants. 12 Data from the Vermont-Oxford Network's database covering a 5-year period at the end of the past decade reveal that survival to discharge among 4172 infants with a birth weight between 401 and 500 g and a gestational age of 23.3 ± 2.1 weeks was only 17%.…”
Section: Resultsmentioning
confidence: 99%
“…18 In more recent studies, none of the infants born at <23 weeks were reported to survive to discharge from the NICU. [19][20] It appears that these findings, and perhaps the practicing neonatologists' own experiences, have influenced the approach to the management provided in the delivery room to the smallest and most immature neonates, as a recent survey of academic and private neonatologists in the United States has found that only 4% of the participants would resuscitate a neonate at 23 weeks' gestation with a birth weight of <500 g. 12 It further states that 57% of the responders would provide comfort care only, and 36% would defer the decision to parental wishes for these extremely immature infants. 12 Data from the Vermont-Oxford Network's database covering a 5-year period at the end of the past decade reveal that survival to discharge among 4172 infants with a birth weight between 401 and 500 g and a gestational age of 23.3 ± 2.1 weeks was only 17%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have noted a wide range of survival rates for all births (including stillbirths) at this gestation, ranging from 0% to 37%. [5][6][7][9][10][11][12]14,[17][18][19]36,37 Some studies present survival rates for live births only, ranging from 0% to 53%. 5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][9][10][11][12]14,[17][18][19]36,37 Some studies present survival rates for live births only, ranging from 0% to 53%. 5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[10][11][12] Survival rates among preterm babies born with GA of 27-28 weeks have been reported to be as high as 90%, although the numbers vary widely across countries. 13 Studies suggest that the incidence and severity of ROP show an inverse relationship with BW and GA, 14 with few cases diagnosed in babies weighing over 1500 g or babies whose GA was 432 weeks at birth. Severe ROP has a higher incidence among infants born with GA o28 weeks or BW o1000 g. However, severe ROP is also reported in babies born at 34-35 weeks with BW 1500 g or more, 15 especially when postnatal systemic complications occur, as shown in studies in India, China, and Lithuania.…”
Section: Discussionmentioning
confidence: 99%